Efficacy of powder formulations of some tropical flora and clay against Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae) on maize in storage - Kingsley Chidi Emeasor; Udeme Etim Jonah; David Nwazuo Enyiukwu (Universitas Lampung, 2023)
A study was carried out to determine the efficacy of three plant materials; pawpaw (Carica papaya) seed powder, kapok tree (Ceiba pentandra) leaf powder, soursop (Annona muricata) leaf powder as well as clay and Permethrin dust against Sitophilus zeamais (Mots.) under laboratory conditions. The experiment was laid out in 5×4 factorial with 5 replicates in Completely Randomized Design in the laboratory. Maize grains weighing 50 g were treated with the plant powders, clay and the synthetic Permethrin at the rate of 0.00 g, 1.5 g, 3.5 g and 5.0 g by weight and then infested with 10 adult weevils in each vial for assessments of adult mortality, F1 emergence and damage. The comparative effectiveness of each of the treatments were assessed by counting weevils’ mortality at 14 days, 28 days, 42 days and 56 days post treatment and progeny emergence at 28 days, 42 days and 56 days post-treatment. The results were subjected to statistical analysis after transforming the data using mean percentage method and the ANOVA, the significant means were separated using the least significant differences test at 5% level. The Permethrin, a synthetic insecticide proved to be very effective followed by clay among all the treatments. Among the botanicals, C. papaya was the most effective followed by A. muricata, but were concentration dependent while C. pentandra was the least or not effective. In all trials, percentage mortality among adult S. zeamais reared on maize treated with Permethrin powders was observed to be the highest (100%) followed by those treated with C. papaya seed powder (56.6%), clay (55.5%) and A. muricata seed powder (38.8%). However, grains treated with powdered leaves of C. pentandra exhibited a low mean percentage mortality of 0.00, 0.20, 0.57 and 0.63, respectively, at different intervals post treatment which was not significantly different when compared with the untreated (control). These percentage mortality among adults were significantly (P<0.05) different from the untreated (control). Thus, all the treatments were found to significantly affect the survival of the S. zeamais at different concentration except in C. pentandra. Effect of plant powder on the emergence of adult S. zeamais was significantly (P< 0.05) different and reduced the F1 progeny emergence. The result indicated that C. pentandra had no significant effect on mortality and F1 emergence of adult S. zeamais (P< 0.05) resulting in severe damage of the grains and weight loss.